STRATEGI GREEN MARKETING BERBASIS DIGITAL YANG BERDAMPAKNYA TERHADAP LOYALITAS KONSUMEN PADA PRODUK RAMAH LINGKUNGAN (DETERJEN BIODEGRADABLE) - Akbarina, Farida; Muslim, Shohib (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of Green Marketing Strategy, Product Quality, and their interaction on Consumer Loyalty in environmentally friendly products, with a focus on biodegradable detergents. This research uses a quantitative approach with a survey method and questionnaires as data collection instruments, involving 100 respondents who are users of environmentally friendly products. The results showed that Green Marketing Strategy has a positive relationship with Consumer Loyalty, but not statistically significant (p> 0.05). Product Quality shows a negative relationship with Consumer Loyalty, which is also not significant (p> 0.05). The interaction between Green Marketing Strategy and Product Quality has a positive influence on Consumer Loyalty, but this influence is not significant (p > 0.05). The conclusion of this study is that Green Marketing Strategy and Product Quality, both individually and together, have not been able to significantly increase Consumer Loyalty. This indicates the need to strengthen marketing strategies, improve product quality, and educate consumers regarding the benefits of environmentally friendly products. Keywords : : Green Marketing Strategy, Product Quality, Consumer Loyalty, Environmentally Friendly Products, Biodegradable Detergent.